The Vampire Diaries : Stefan Diaries the Compelled Vol. 6 - Smith .L .J (Lisa J.); Develooped by Kevin Williamson & Julie Plec (New York HarperTeen, 2012)
Stefan Salvatore, on a mission to save his brother Damien from Samuel, a vampire from Katherine's past, decides to form an alliance with a coven of witches, but soon realizes Samuel has a plan to gain unlimited powers and they may be in more danger than he thought.
Keywords: Vampires -- Brothers -- Witches -- Paranormal fiction -- Interpersonal relations -- Triangles (Interpersonal relations) -- Young adult fiction -- England--London